(untitled) (Revista da Faculdade de Odontologia - UPF, 2015)
Objective: The aim of this study was to evaluate the effectiveness of Passive Ultrasonic Irrigation (PUI) with different solutions to calcium hydroxide (Ca(OH)2) removal. Methods: Forty-eight single-rooted mandibular premolar were prepared and filled with Ca(OH)2. After 15 days, the specimens were randomly divided into four groups according to the method of removal of the intracanal medication (n=12). In Group 1, Ca(OH)2 removal was performed through conventional irrigation with 2,5% NaOCl and 17% EDTA combined with the use of the ‘master apical file’ at working length. Groups 2 and 3 were treated in the same manner as Group 1, following the PUI with 2,5% NaOCl and 17% EDTA, and 2,5% NaOCl and 10% citric acid, respectively. Group 4 served as a control group and received no intracanal medication. The roots were grooved longitudinally and split in two halves. The half with the higher remaining amount was analyzed with a stereomicroscope and the percentage of surface area covered by the remaining Ca(OH)2 in relation to the surface area of each third and total root canal was calculated. The results were statistically analyzed with the Kruskal-Wallis Test and Mann-Whitney Test with null hypothesis set as 5%. Results: None of the groups tested showed similarity with the control group (P < 0.05). However, no statistical difference was observed between the removal techniques of Ca(OH)2 from root canals. Conclusions: The suggested protocols were similar. Neither syringe irrigation nor the combination of syringe irrigation with PUI were effective methods for removing Ca(OH)2 from the root canals.